Sovereign erotics: A collection of Two-Spirit literature - Driskill, Qwo-Li; Justice, Daniel Heath; Miranda, Deborah; Tatonetti, Lisa (The University of Arizona Press, 2011)
Les personnes bispirituelles, identifiées par de nombreux noms et positions tribales spécifiques au sein de leurs communautés, vivent, aiment et créent de l'art depuis des temps immémoriaux. Ce n’est cependant que dans les années 1970 que la littérature autochtone queer contemporaine a attiré l’attention du public. Même aujourd’hui, seule une poignée de livres en parlent spécifiquement, notamment la collection de 1988 Living the Spirit: A Gay American Indian Anthology. Depuis la publication de ce livre il y a vingt-trois ans, aucune autre collection n'a été publiée se concentrant explicitement sur l'écriture et l'art des peuples autochtones bispirituels et queer. Cette collection historique s'efforce de refléter la complexité des identités au sein des communautés autochtones gaies, lesbiennes, bisexuelles, transgenres, queer et bispirituelles (GLBTQ2). Rassemblant le travail d'écrivains confirmés et de nouvelles voix talentueuses, cette anthologie couvre les genres (fiction, non-fiction, poésie et essai) et les thèmes (mémoire, histoire, sexualité, indigénéité, amitié, famille, amour et perte) et représente un tournant décisif. moment dans les littératures amérindiennes et autochtones, les études queer et les intersections entre les deux. En collaboration, les pièces de Sovereign Erotics démontrent non seulement la diversité radicale des voix des écrivains autochtones GLBTQ2 d'aujourd'hui, mais également la beauté, la force et la résilience des personnes autochtones GLBTQ2 au XXIe siècle. Contributeurs : Indira Allegra, Louise Esme Cruz, Paula Gunn Allen, Qwo-Li Driskill, Laura Furlan, Janice Gould, Carrie House, Daniel Heath Justice, Maurice Kenny, Michael Koby, M. Carmen Lane, Jaynie Lara, Chip Livingston, Luna Maia , Janet McAdams, Deborah Miranda, Daniel David Moses, DM O'Brien, Malea Powell, Cheryl Savageau, Kim Shuck, Sarah Tsigeyu Sharp, James Thomas Stevens, Dan Taulapapa McMullin, William Raymond Taylor, Joel Waters et Craig Womack
Keywords: amérique du nord; amériques; approches et analyses; arts; discipline; discours dominant; féminisme autochtone; identités LGBTQIA2+; outils; ouvrages de références; queer; racisme; régions géographiques; système colonial; systèmes d'oppressions; études littéraires

Ogimah Ikwe: Native Women and Their Path to Leadership - Lajimodiere, Denise K. (Wicazo Sa Review, 2011)
Much documentation gathered on Native American women's activities originated in the journals of European male missionaries and explorers. These first visitors observed Native societies through the eyes of their own culture, a culture in which male activities were the only happenings of note. 1 This bias led to indirect and distorted descriptions of Native American women's activities and beliefs. 2 Scholars who study Native American women today have made significant inroads into their histories; however, many interpretations remain incorrect and undeveloped. Devon Mihesuah states, "Because many authors write from a patriarchal or white feminist perspective, the value of Indian women is vastly underrated." 3 Gretchen Bataille and Kathleen Sands address this shortcoming, saying, "The portrayal of American Indian women in North America over the last four centuries offers an uneven body of documentary evidence about the lives of Native women as individuals and members of their group." This study's purpose is to increase the visibility of Native American women in leadership roles by recording the voices and histories of nine Native American women leaders. It focuses on the experiences, perceptions, and beliefs of the women interviewed, giving a voice to nine of today's Native American female leaders, nine Ogimah Ikwe (leader women).
Keywords: 1900-1999; 1940-1949; 1950-1959; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; amériques; approches et analyses; care; cours; discipline; discours dominant; femmes* au pouvoir; femmes* autochtones; féminisme autochtone; histoire et politique; patriarcat; pol4105; premier cycle; premières nations; périodes historiques; rapports sociaux de sexe; régions géographiques; sciences de l'éducation; système colonial; systèmes d'oppressions; thématiques; travail; états-unis

Law Reform, Lesbian Parenting, and the Reflective Claim - Leckey, Robert (Social & Legal Studies, 2011)
The article aims to complicate efforts to make law fit or catch up to social practices. It scrutinizes the ‘reflective claim’ using the case study of recognition of parenting by lesbian couples. Reforms in the United Kingdom’s Human Embryology and Fertilisation Act 2008 and the Canadian province of Quebec’s civil code are compared with empirical work from the social sciences on lesbians’ family practices. The reflective claim rests on problematic ideas about social practices and law. Since law is always blunt and incomplete, choices must be made as to which practices it should aim to recognize. Furthermore, the impact of heterosexist and homophobic conditions on lesbian families means that observable practices may not be a suitable model for gay-affirmative reforms. As advanced in the literature, the reflective claim overlooks law and society’s complex interaction, including how reform will not merely reflect but also alter practices. It fails to do justice to law reform’s normative character, obscuring its costs and positive potential
Keywords: 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; amérique du nord; amériques; angleterre; approches et analyses; canada; corps; cours; discipline; discours dominant; droit; droit des femmes*; europe; hétérosexisme; identités LGBTQIA2+; inégalités; maternité; parentalité; premier cycle; périodes historiques; queer; québec; régions géographiques; science politique et droit; sciences humaines; soc2264; sociologie; systèmes d'oppressions; thématiques

BLOOD UNDER THE BRIDGE: REFLECTIONS ON “THINKING SEX” - Rubin, Gayle (GLQ: A Journal of Lesbian and Gay Studies, 2011)
This article reflects on the intellectual and political circumstances of the publication of Gayle Rubin's 1984 essay “Thinking Sex: Notes for a Radical Theory of the Politics of Sexuality.” In particular, the article considers the context of the feminist “sex wars” of the late 1970s and early 1980s, offering a detailed account of several of the period's key events, publications, and debates. The article also reflects on the relation between this moment in the history of feminism and the history of GLBT and queer scholarship over the past several decades.
Keywords: 1900-1999; 1960-1969; 1970-1979; LGBTQIA2+; amériques; approches et analyses; cours; discipline; discours dominant; féminisme pro-sexe; histoire et politique; militance; philosophie; premier cycle; périodes historiques; queer; régions géographiques; sciences humaines; sex wars; soc2014; systèmes d'oppressions; thématiques; travail; violences; états-unis; études de genres